2020
DOI: 10.3390/jmse8040298
|View full text |Cite
|
Sign up to set email alerts
|

Soil Interaction and Grout Behavior for the NREL Reference Monopile Offshore Wind Turbine

Abstract: Monopiles for offshore wind are the most used foundations by farm operators due to their low production costs, when compared to other bottom-fixed or floating foundations. In this research, a monopile foundation for offshore wind power was evaluated for its soil interaction and grout behavior, and an appropriate numerical model for the structural analysis of the foundation and tower was developed. FAST 8, an aero-hydro-servo-elastic numerical code developed by NREL, was used to obtain the loads applied on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Therefore, the DS method was used to economize the analysis process. The DS method was applied through the nonlinear spring element (COMBIN39) [43] for both lateral and vertical directions, as illustrated in Figure 4. COMBIN39 is capable of describing the nonlinear relationship between compression and tension stiffness (force-displacement) for transversal or torsional directions.…”
Section: Setting Up the Analysis Modelmentioning
confidence: 99%
“…Therefore, the DS method was used to economize the analysis process. The DS method was applied through the nonlinear spring element (COMBIN39) [43] for both lateral and vertical directions, as illustrated in Figure 4. COMBIN39 is capable of describing the nonlinear relationship between compression and tension stiffness (force-displacement) for transversal or torsional directions.…”
Section: Setting Up the Analysis Modelmentioning
confidence: 99%
“…Dynamic analyses were performed using implicit-explicit switching, with an initial implicit analysis to preload the structure, followed by dynamic excitation using the explicit solver, and finally followed by an implicit analysis to obtain the post-earthquake monotonic response. This numerical modelling scheme was chosen following work by Asnaashari et al 22 and Vieira et al 23 who demonstrated the effectiveness of 3D FE analysis to model grouted connections under static loads. Natural frequencies and modeshapes were determined using the Block Shift and Invert Lanczos method.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Figure 8 shows the spring stiffness curves for the undamaged state. In other words, the pile is supported by a series of nonlinear elastic springs, which simulate soil reactions, and the unloading occurs along the same loading curve (Carswell et al., 2015; Vieira et al., 2020). The considered damage was scouring (Devriendt et al., 2014; Prendergast et al., 2015), that is, erosion of the mudline near the foundation.…”
Section: Application 2: Owt Structurementioning
confidence: 99%